Close encounters of the microbial kind everything you need to know about common infections - Wilson, Michael 1947-; Wilson, Philippa J. K. (Springer, 2021)
Microbes – can’t live with them, can’t live without them. Increasingly, we’re finding out that our microbiota (the microbes that live on us) are essential for our wellbeing – they provide us with nutrients and vitamins and play a key role in developing our immune system. On the other hand, they are responsible for a great deal of misery, as they are major causes of death and debility around the world. As well as our own microbiota turning against us, there are lots of other microbes out in the wider world that can seriously damage, or even kill, those they infect. The current pandemic of COVID-19 shows the devastating effect that an infectious disease can have – our lives have been turned upside down.If you live in a developed country, you’re not likely to get killer diseases such as ebola and cholera, but you do have a high chance of catching other infections that can have a significant impact on your wellbeing. This book focuses on those infections you’re most likely to go down with, and supplies the answers to the following questions about them: - Which infectious diseases are we likely to come across?- How common are they? - What microbes cause them? - What happens to our bodies during an infection? - How are the resulting illnesses treated?- How can we avoid getting them? This book covers nearly 60 infectious diseases that people living in developed countries are likely to experience at some point during their life. It also has an introductory chapter that describes, in everyday language, the basic principles of microbiology and infectious diseases. Each chapter is lavishly illustrated, has interesting, relevant inserts, and provides a list of web-accessible suggestions for further reading